Consumers’ intention to purchase counterfeit branded goods in Klang Valley / Saidatul Nur Athirah Sahril - Sahril, Saidatul Nur Athirah (Faculty of Business and Management, 2020)
Counterfeiting activities is an illegal activity that can be found easily at any place especially in Malaysia. This study hopes to provide more information on consumers’ intention to purchase counterfeit branded goods in Klang Valley that is yet to be discovered. A descriptive study is being conducted for this research whereby data is being collected from 203 respondents. Five-point Likert scale questionnaires are being distributed to the respondents among consumers in Klang Valley and convenient sampling was used in this research (Sekaran and Bougie, 2003). The data obtained is being analyzed using Reliability Test, Pearson Correlation Coefficient Statistics, and Multiple Regression Analysis was conducted in this research. The objectives of this study are to know whether there is significant relationship between attitude, subjective norm, perceived behavioral control, brand consciousness and consumers’ intention to purchase counterfeit branded goods in Klang Valley. The result from the study indicate that two independent variables which is attitude and subjective norm had a significant relationship towards intention to purchase counterfeit branded goods while the most influential determinants towards intention to purchase counterfeit branded goods is subjective norm.